Rolston over the years: summary of the career of Holmes Rolston III - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2024)
This is a summary of the career of Holmes Rolston III across forty years at Colorado State University, his teaching, travels and invited lectures over all seven continents, his interactions with students and colleagues, his numerous wilderness adventures on every continent. Rolston was a celebrated naturalist, the first and for decades the only University Distinguished Professor at CSU who was not a scientist.
A summary of the career of Holmes Rolston III
The document herewith extends several hundred pages, and can be scanned and searched. Some images are not captioned.
Keywords: Rolston, Holmes, 1932-2025; philosophy; theology; environmental ethics; biology; intrinsic value